2008
DOI: 10.1007/s00449-008-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser scanning microscopy as an analytical tool in chromatographic research

Abstract: In recent years, confocal laser scanning microscopy has been developed into a non-invasive tool to probe intra-particle profiles of protein in chromatographic adsorbents. A necessary prerequisite when using this technique lies in the labeling of proteins with fluorescent probes. The quality of the obtained results is thus strongly dependent on the probes used, its sensitivity on experimental parameters and the change of protein characteristics upon binding. In this review, the fundamental issues when using flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…However, poorly transparent ("opaque") supports present a problem. Soaking the support with liquid of comparable refractive index is a possible solution to enable direct measurements also in such cases [12,62,63]. Evidence from CLSM studies on the interaction of proteins with chromatographic supports can be translated almost directly to enzyme immobilization [50,62,[71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Direct Visualization Of Protein Distribution In Solid-suppormentioning
confidence: 97%
See 1 more Smart Citation
“…However, poorly transparent ("opaque") supports present a problem. Soaking the support with liquid of comparable refractive index is a possible solution to enable direct measurements also in such cases [12,62,63]. Evidence from CLSM studies on the interaction of proteins with chromatographic supports can be translated almost directly to enzyme immobilization [50,62,[71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Direct Visualization Of Protein Distribution In Solid-suppormentioning
confidence: 97%
“…Layers thus prepared were then analyzed microscopically. Confocal laser scanning microscopy (CLSM) has significantly advanced the analysis of proteins in intact porous supports (Table 2) and researchers in protein chromatography were forerunners in this respect [62][63][64][65][66][67][68][69][70]. CLSM offers spatial resolution at a length scale well suitable for the characterization of enzyme immobilizates and it is conveniently used even by nonspecialists.…”
Section: Direct Visualization Of Protein Distribution In Solid-suppormentioning
confidence: 99%
“…The paper of Jürgen Hubbuch, head of this group, and Maria-Regina Kula, one of the long-term cooperation partners of Christian Wandrey (together they received the Enzyme Engineering Award in 1995) reviews fundamental issues of making use of the confocal laser scanning microscopy as an analytical tool in chromatographic research and gives a critical evaluation on published literature in this field [5]. The following contribution of Jörg Thömmes (Biogen Idec Corporation, Cambridge, USA), a former PhD-student of Christian Wandrey and former head of the bioseparations group at the then-neighboring Institute of Maria-Regina Kula in Jülich shows how modeling can help to understand the hydrophobic interaction chromatography separation mechanism [9].…”
Section: Weuster-botz (And)mentioning
confidence: 99%
“…We will discuss this issue in more detail later in the paper. Hubbuch and Kula (2008), Susanto et al (2006Susanto et al ( , 2007, and Yang et al (2006) reported light attenuation (the loss of light intensity inside chromatography beads) when utilizing confocal laser scanning microscopy to study intraparticle phenomena. The degree of attenuation depends on the bead material and the excitation and emission wavelengths.…”
Section: Methodsmentioning
confidence: 97%
“…In recent years, confocal laser scanning microscopy has emerged as a powerful tool to probe intraparticle biological interactions (Hubbuch and Kula 2008) and facilitate in situ characterization of porous beads. Confocal microscopes use a pinhole with a distinct aperture to eliminate out-offocus light or glare in samples whose thickness exceeds the depth of view.…”
Section: Introductionmentioning
confidence: 99%